Description of two new species in the genus Glyphodes Guenée from Indonesia (Lepidoptera: Crambidae, Spilomelinae) - Watung, Jackson F.; Darmawan, Darmawan; Suwito, Awit; Narakusumo, Raden Pramesa; Nugroho, Hari; Encilia, Encilia; Qodri, Agmal; Peggie, Djunijanti; Ubaidillah, Rosichon; Sutrisno, Hari (Zootaxa, 2024)
Two new species of Glyphodes Guenée, 1854 from Indonesia are proposed as new to science, namely G. nurfitriae sp. nov. and G. ahsanae sp. nov. The total number of recorded Glyphodes for Indonesia is 48 at present. Images of adults and genitalia are provided for both new species.